(untitled) (Journal on studies and research of academic knowledge, 2019)
The objective of this research was to analyze the strengths and weaknesses of the curricular and pedagogical aspects of linguistic and methodological training of future English as a second language teachers at the National University of Itapúa. It is a qualitative and quantitative study because graduates’ perception of the program was analyzed and the results of the linguistics analysis were quantified. Likewise, a review of documents related to undergraduate objectives and curriculum of the undergraduate profile and the curriculum was performed in order to identify strengths and weaknesses. Six out of 13 graduates from 2011 to 2105 took part in the study and a survey with closed and open questions was conducted to determine their perception of the program. The results suggest that 5 of the 6 graduates, representing 83% of the graduates surveyed have a proficiency in the English language running from good to excellent, which confirms the excellent organization of the curriculum and teaching aspects of undergraduate study. In conclusion, even though graduates reported having basic skills training, they indicated the need to include more specific subjects related to language training in the program with subjects such as phonology, phonetics and grammar. Lastly, it is proposed to carry out a reform and reorganization of the curriculum with the addition of the subjects referred to without changing the number of hours and specialized courses in English phonetics and grammar are recommended in order to complement the continuous training of graduates in the English language.